Rise of Mobile Commerce Business Modernizing Ecommerce business with personalization and transparency - Keerthi kethineni , K Anitha , G Satish Kumar (International Journal of Advanced Science and Technology, 2020)
E-commerce is the new-age business strategy to engage users online. As the time spent on mobile devices is doubled year on year, every prominent brand is trying to grab the attention of online users. Despite the industry and business verticals, E-commerce has changed the face of online sales and marketing methods. This paper focuses on next-generation shopping experience Mobile Commerce (M-Commerce) and its impact, exponential growth by 2020 and beyond. Keywords: M-Commerce,E-Commerce.